1976
DOI: 10.1302/0301-620x.58b2.932076
|View full text |Cite
|
Sign up to set email alerts
|

The shelf operation for hip dysplasia in adolescence

Abstract: Failure of normal acetabular development is inevitable in congenital dislocation of the hip when it is unrecognised until late infancy or early childhood. Numerous stabilising procedures have been described, one of the first being the shelf operation or acetabuloplasty. This procedure fell into disrepute because the shelf was often located too high or was too small to prevent upward migration of the femoral head. The technique described emphasises the importance of resecting the thickened capsule and exposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Good results in 60-85% of cases after relatively short follow-up have been reported (Bjøro 1956, Wilson 1974, Wainwright 1976) but there seems to be a gradual failure of the operation with time. Summers et al (1988) had a mean follow-up of 16 years and found good results in 59% of cases, which is consistent with the good effect in 10 of the 14 hips in this study.…”
Section: Late Surgical Proceduresmentioning
confidence: 96%
“…Good results in 60-85% of cases after relatively short follow-up have been reported (Bjøro 1956, Wilson 1974, Wainwright 1976) but there seems to be a gradual failure of the operation with time. Summers et al (1988) had a mean follow-up of 16 years and found good results in 59% of cases, which is consistent with the good effect in 10 of the 14 hips in this study.…”
Section: Late Surgical Proceduresmentioning
confidence: 96%
“…Various surgical procedures, including the Salter, Pemberton, Steel, and Tönnis osteotomies and shelf acetabuloplasty, have addressed the different pathologic components of the dysplastic hip. However, their success rates based on radiographs and self-reported patient outcomes have been variable [8,16,26,32,33,39,43,44,46] and the choice for the optimal surgical procedure to correct acetabular dysplasia continues to be controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The shelf operation has been a major surgical option in children over 8 years old to provide adequate support to the subluxated femoral head and ensure a stable mobile joint capable of standing. [2][3][4][5] It is necessary to provide the biomechanical guideline for optimal surgical parameters of the shelf surgery.…”
Section: Introductionmentioning
confidence: 99%